2016
DOI: 10.1155/2016/6961202
|View full text |Cite
|
Sign up to set email alerts
|

Essure Surgical Removal and Subsequent Resolution of Chronic Pelvic Pain: A Case Report and Review of the Literature

Abstract: Background. Hysteroscopic tubal sterilization (Essure) is a minimally invasive option for permanent contraception with high reported rates of patient satisfaction. A small percentage of these women subsequently choose to have the tubal inserts removed due to regret or perceived side effects such as late-onset pelvic pain secondary to placement of the Essure device. Case. A twenty-nine-year-old woman G4P4014 presented with a two-year complaint of chronic pelvic pain and dyspareunia after the hysteroscopic place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Pelvic pain is the main symptom described. This potential side effect has been reported in the literature and can be due to the misplacement of the device [5]. Yunker reported an incidence of 8.1% regarding acute pelvic pain after hysteroscopic sterilization and an incidence of 4.2% regarding persistent pain 3 months or greater after hysteroscopic sterilization [4].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Pelvic pain is the main symptom described. This potential side effect has been reported in the literature and can be due to the misplacement of the device [5]. Yunker reported an incidence of 8.1% regarding acute pelvic pain after hysteroscopic sterilization and an incidence of 4.2% regarding persistent pain 3 months or greater after hysteroscopic sterilization [4].…”
Section: Discussionmentioning
confidence: 91%
“…Essure ® is a minimally invasive option for permanent contraception with high reported rates of patient satisfaction [5]. Some women subsequently choose to have inserts removed for perceived side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pelvic pain continued to worsen until she requested to have the device removed through a laparoscopic bilateral total salpingectomy. After removal, the patient conclusively reported that the chronic pelvic pain resolved itself [ 11 ]. It is possible that her pain was related to this device as well.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case reports demonstrate pain due to Essure misconfiguration or perforation with subsequent resolution of symptoms after device removal. 18,20,21 A case study by Alcantara and colleagues described a patient with chronic pelvic pain and an Essure coil that was curved in an elliptical shape, not adhering to the anatomic course of the fallopian tube. The patient reported pain resolution after laparoscopic removal of the device.…”
Section: Workup and Evaluationmentioning
confidence: 99%